Lunar tides in earth current at Barrow (MAUSAM, 1972)
The lunar tides in earth current (viz., Telluric current) at Barrow (71° 18'N, 156°47'W) have been studied by using hourly values of N-S and E-W components for the period 1963-1965 and 1961-1962, respectively. The study shows that significant results can be obtained from data for even short periods of Telluric current. Further it has been found that there is good agreement between lunar semi-diurnal oscillations in earth currents (studied by Egedal and Rougerie) and Telluric current (present study).